The Chemogenetic Receptor Ligand Clozapine N-Oxide Induces in vivo Neuroreceptor Occupancy and Reduces Striatal Glutamate Levels - Bærentzen, Simone; Casado-Sainz, Agata; Lange, Denise; Shalgunov, Vladimir; Tejada, Isabel Martinez; Xiong, Mengfei; L’Estrade, Elina T.; Edgar, Fraser G.; Lee, Hedok; Herth, Matthias M.; Palner, Mikael (Frontiers in Neuroscience, 2019)
Chemogenetic studies with the ligand clozapine N-oxide (CNO) are predicated upon the assumption that CNO is devoid of actions at natural neuroreceptors. However, recent evidence shows that CNO may be converted back to clozapine (CLZ) in vivo, which could yield plasma concentrations that may be sufficient to occupy inter alia dopamine D2/3 and serotonin 5HT2A receptors in living brain. To test this phenomenon, we measured striatal dopamine D2/3 receptor occupancy with [18F]fallypride PET and serotonin 5HT2A occupancy ex vivo using [18F]MH.MZ. We found a CNO dose-dependent effect on the availability of both neuroreceptor sites. In parallel MR spectroscopy experiments, we found that CNO reduced creatine + phosphcreatine (Cr+PCr) and increased N-acetylaspartate + N-acetylaspartylglutamate (NAA+NAAG) signals in the prefrontal cortex, and also reduced the glutamate signal in dorsal striatum, with peak effect at 2 mg/kg. Thus, our findings suggest that conversion of CNO to CLZ in living rats imparts significant occupancy at endogenous neuroreceptors and significant changes to neurometabolite levels.